2021
DOI: 10.1016/j.msard.2021.102988
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20 antibody therapy and risk of infection in patients with demyelinating diseases

Abstract: Background: Anti-CD20 antibody therapy may be associated with an increased risk of infections. We therefore investigated risk factors for infection in patients with demyelinating diseases treated with anti-CD20 antibody therapy. Methods: In this retrospective uncontrolled study, patients ever treated with anti-CD20 antibodies at an academic clinic were identified through the Danish Multiple Sclerosis Registry (DMSR). Data were collected from medical charts and the DMSR. We assessed occurrence of severe infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 36 publications
5
28
0
4
Order By: Relevance
“…Regarding serum immunoglobulins in the four groups of patients, ocrelizumab induced a decrease in serum IgM levels, with no changes in IgG values, as previously reported for patients treated with anti-CD20 antibodies ( 9 , 20 ). Likewise, all groups of patients showed a decrease in the IgG/IgM and IgA/IgM ratios.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding serum immunoglobulins in the four groups of patients, ocrelizumab induced a decrease in serum IgM levels, with no changes in IgG values, as previously reported for patients treated with anti-CD20 antibodies ( 9 , 20 ). Likewise, all groups of patients showed a decrease in the IgG/IgM and IgA/IgM ratios.…”
Section: Discussionsupporting
confidence: 81%
“…( Seery et al, 2021 Aug ) Another study showed that pwMS with an infection requiring hospitalization were older, more commonly had comorbidities, had longer duration of treatment and higher EDSS scores. ( Oksbjerg et al, 2021 Jul ) Similarly, we have also shown that older age increases the risk for infections requiring hospitalization. In our cohort we didn't find association between IgG levels and infections, however, we found that smaller drop in IgM before 3 rd ocrelizumab cycle increased the risk for infection requiring hospitalization.…”
Section: Discussionmentioning
confidence: 66%
“…( Seery et al, 2021 Aug ) Data from the Danish MS registry showed that the rates of low levels of IgM and IgG among pwMS treated with CD20 depleting therapies (rituximab, ocrelizumab and ofatumumab) were 28% and 5%, respectively. ( Oksbjerg et al, 2021 Jul ) Overall, the largest body of evidence related to immunoglobulin levels exists for rituximab. When looking at the different classes of immunoglobulins, IgM was the most frequently affected immunoglobulin whose levels tend to stay low for longer periods than IgG after rituximab cessation and often remain low even after the level of B cells have returned to normal.…”
Section: Discussionmentioning
confidence: 99%
“…Infektionen bergen generell ein Risiko für MS-Patienten, da sie nicht nur einen Pseudoschub auslösen können, sondern auch mit Krankheitsprogression und reduzierter Lebenserwartung assoziiert sind [ 40 , 46 , 82 ]. Dieses infektionsassoziierte Risiko kann sich durch entsprechende Begleiterkrankungen und krankheitsmodifizierende Therapien (DMTs) nochmals weiter erhöhen [ 23 , 39 , 54 , 62 , 81 ]. Darüber hinaus existieren verschiedene Theorien zur Beteiligung von Infektionen an der Immunpathogenese der MS. Diese umfassen u. a. folgende Mechanismen: „molecular mimicry“, „bystander activation“ und „epitope spreading“ [ 44 ].…”
Section: Einführungunclassified